Antimicrobial properties of ethanolic extract from gac fruit (Momordica cochinchinensis Spreng.) powder composed of pulp and aril - Krishantinee, Gobi; Vadiveloo, Sajetra Devi; El-Enshasy, Hesham Ali; Dailin, Daniel Joe; Dennis Chew, Sing Teong; Nor Hasmaliana, Abdul Manas (Malaysian Institute of Chemistry, 2026)
The growing prevalence of antimicrobial-resistant pathogens necessitates the exploration of safer and more sustainable natural alternatives to conventional therapeutics. Gac fruit (Momordica cochinchinensis Spreng), noted for its phenolic-rich composition and inherent antimicrobial potential, offers a promising source of bioactive compounds whose functional properties can be preserved through appropriate post-harvest processing such as lyophilization. This study investigates the antimicrobial properties of ethanolic extracts obtained from lyophilized-powder and paste of Gac fruit pulp and aril, with a particular emphasis on the sample exhibiting the highest total phenolic content (TPC). Both the pulp-aril paste and the powder forms of Gac fruit underwent Soxhlet extraction, and their TPC was determined using the Folin-Ciocalteau assay. The powdered form demonstrated a slightly higher TPC (21.901 μg GAE/mg) compared to the paste counterpart (18.750 ± 0.019 μg GAE/mg). Minimum bactericidal concentration (MBC) and minimum inhibitory concentration (MIC) measurements were used to evaluate the antibacterial properties of the extract against nine opportunistic pathogens. The results indicated variable levels of susceptibility: Escherichia coli required the highest extract concentration (50 mg/mL) for bactericidal activity, whereas Aspergillus oryzae was the most susceptible, with both MIC and MBC at 8.33 mg/mL. These findings demonstrate that the phenolic content and antimicrobial activity of Gac fruit are largely retained following lyophilization, highlighting the relevance of this post-harvest technique for preserving bioactive quality in industrial processing. The preserved antibacterial properties underscore the potential of Gac fruit as a source of plant-based antimicrobial agents. Further work is needed to refine extraction conditions and exploresynergistic interactions with existing antimicrobials to enhance overall efficacy.